CT angiography of the coronary arteries: setting new diagnosticstandards in cardiovascular medicine - Cademartiri, F.; Palumbo, A.; Maffei, E.; Martini, et al., C. (Acta Biomedica Atenei Parmensis, 2009)
CT Coronary Angiography of the heart is one of the fastly developing techniques in cardiovascular imaging. It is rapidly emerging and quickly entering the clinical practice and international guidelines. The increasing evidence regarding the strong role in the assessment of coronary artery lumen is progressively expanded by evidences of the important role of coronary wall imaging. The prognostic importance of CT Coronary Angiography is worldwide reported and the main question that is posed at the moment concerns the potential impact in primary prevention. In this review we will discuss the current applications and technology state of the art, X-ray dose issues, the training requirements and implementation in the healthcare context of CT Coronary Angiography.